94.2k views
2 votes
Could someone help me please!!

Could someone help me please!!-example-1
User Gilbert
by
5.0k points

2 Answers

1 vote

Answer:

3333333333 the answer is 3

Explanation:

User Jack The Baker
by
5.3k points
7 votes

Answer:

Option C.

Explanation:

The given expression is
(x^(y))/(x^(3))=x^(6)

We have to solve the expression for the value of y.


x^(y)* x^(-3)=x^(6) [Since
x^(a)* x^(b)=x^(a+b)]


x^(y-3)=x^(6)

y - 3 = 6 [By equating the powers of same base]

y = 6 + 3

y = 9

Therefore, Option C is the answer.

User Kiechlus
by
5.7k points